Evaluasi Kondisi Transformator Daya PLTU Tenayan Raya Menggunakan Metode Sweep Frequency Response Analysis: Power Transformer Condition Assessment at Tenayan Raya Power Plant Using Sweep Frequency Response Analysis - Firdaus; Mario Johannes Marpaung; Boy Ihsan; Nurhalim; Dian Yayan Sukma (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2025)
Transformers are one of the most important equipment in electrical power systems. Transformer failure at power plants can interrupt the continuity of electricity supply. Therefore, monitoring the condition and early detection of transformer damage is important to ensure that transformers can work properly until their maximum service life. One type of damage that can occur is a change in the mechanical structure of the transformer's internal components. This damage can be detected using the Sweep Frequency Response Analysis (SFRA) method, which is a non-invasive testing technique that analyzes changes in frequency response due to internal mechanical disturbances. This study conducted an SFRA analysis on power transformers at the Tenayan Raya Power Plant by comparing the conditions before and after repairs. Comparisons across three test periods showed that the most notable variations occurred between 2020 and 2022, mainly at high frequencies, indicating winding deformation due to operational stress. In contrast, the pre- and post-maintenance comparison revealed stable responses, confirming that maintenance activities did not cause significant deformation.